World's major cereals share common ancestry - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Work in Britain and Japan has shown that the order of the genes of the chromosomes of wheat and rice, which diverged some 60 million years ago, is essentially the same. Preparing gene maps is a very costly exercise with no certain outcome, but this...